PENYEDIAAN RUANG UNIT KEGIATAN MAHASISWA (UKM) - Patrick Marcell Fandy; Alfian Adie Chandra; Heri Dua Lembang; Rosalina Revassy; Handoko Handoko; Marcelino Yonas; Karl Karolus Wagab Meak; Tiper Korneles Muwarberto Uniplaita (LPPM Uncen, 2023)
The implementation of the construction of Unit Kegiatan Mahasiswa (UKM) room at the Faculty of Engineering, Cenderawasih University is a form of support for the appeal of the Ministry of Education, Culture, Research, and Technology (KEMENDIKBUD RISTEKDIKTI) as stated in the Guidelines for the Implementation of Student Organization Activities No. 0241/E/E2/KM.09.00/2022. Student activities under student organizations are a forum for students to develop their capacity as students in the form of aspirations, initiations, or positive, and creative ideas through participation in various relevant activities. The purpose of this service activity is to provide a UKM building for each Department Student Association (Himpunan Mahasiswa Jurusan–HMJ) as a forum for implementing student activities at the Faculty of Engineering, Cenderawasih University. The realization of the UKM building construction activities was carried out through four stages of work. First, budget design by setting a format of 80% of the total cost for the main building fund and 20% for emergency funds. Second, the design of the UKM building is adjusted to the dedicated fund. Third, procurement of materials and building worker services. Fourth, the SME building construction process. The contribution of this activity is the design and construction of the UKM building at the Faculty of Engineering, Cenderawasih University as a means for students to channel their aspirations, to develop their science and technology abilities and organizational potential.Keywords: Student activity units; student centers; learning students; student organizations; student affairs